2012
DOI: 10.1093/carcin/bgs373
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in a hsa-let-7 binding site in RAD52 is associated with breast cancer susceptibility

Abstract: Genetic variants may influence miRNA-mRNA interaction through modulate binding affinity, creating or destroying miRNA-binding sites. Twenty-four single nucleotide polymorphisms (SNPs) that were predicted to affect the binding affinity of breast cancer-related miRNAs to 3'-untranslated regions (UTR) of known genes were genotyped in 878 breast cancer cases and 900 controls in Chinese women. Three promising SNPs (rs10494836, rs10857748 and rs7963551) were further validated in additional 914 breast cancer cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 46 publications
(41 reference statements)
1
23
0
Order By: Relevance
“…Such a scenario has been described for BRIP1. SNPs in the 3'-UTR of BRIP1 have been shown to influence mRNA stability and regulate gene expression (Jiang et al, 2013). As a result, these SNPs may affect genetic susceptibility to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Such a scenario has been described for BRIP1. SNPs in the 3'-UTR of BRIP1 have been shown to influence mRNA stability and regulate gene expression (Jiang et al, 2013). As a result, these SNPs may affect genetic susceptibility to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that single nucleotide polymorphisms (SNPs) related to miRNAs may either create or disturb miRNA target interactions, and induce diverse functional consequences1920212223. Thus, in this study, we performed the genotyping of several potentially functional SNPs in let-7 and Lin28 and assessed their associations with risk of oral cavity cancer in an ongoing hospital-based case-control study of 384 cases and 731 cancer-free controls in a Chinese Han population.…”
mentioning
confidence: 99%
“…In 2008, Brendle et al indicated that there is a highly-strong association between the A allele of rs743554, within ITGB4 3 0 UTR, and the increased risk of ER-negative breast cancer [39]. Moreover, the homozygote (C/C) and heterozygote (A/C) genotypes of rs4245739 in MDM4 3 0 UTR, as well as the rs7963551 C allele in RAD52 3 0 UTR have been displayed to be associated with reduced breast cancer risk [40,41]. The single study analyzing an ErbB4 miRNA-related SNP in breast cancer showed that rs1595066 is associated with the decreased risk of breast cancer [19].…”
Section: Discussionmentioning
confidence: 99%